Optimisation of tilt angles for fixed PV Panel via computational algorithm - Tang, Hong Wei (2022)

(untitled)
Solar energy is one of the clean, renewable, and unlimited energy sources which has the potential to fulfil global energy demand in the future time. To maximise the power generation, PV panels are often integrated with sun-tracking system to track the position of the sun to ensure the PV panels’ surface are always perpendicular to the incoming sunray. On the other hand, it entails more maintenance and operational expenses by using a single-axis or dual-axis tracking system. Since the aim is to entice investors to invest in solar PV systems, it is advised that the fixed-PV panel, which does not include a sun tracking device, can be used to reduce the investment cost. Even though much research and analysis have been conducted and studied in relation to determining the optimal angles for fixed-PV panels, there are relatively few studies connected to Malaysia. Therefore, this Final Year Project (FYP) proposes and develops a computational algorithm to calculate the annual energy generation at different tilt angles of the PV panel and determine the optimum tilt angles of the PV panel at various locations in Malaysia under local weather conditions. Ultimately, a Graphical user interface (GUI) application was also developed to assist the user in obtaining the outcomes. The investigation was performed based on simulation using MATLAB® (R2021a), and the Weather Data files were all obtained from JRC Photovoltaic Geographical Information System (PVGIS). To present a more accessiblemanner for the user to evaluate, polar contour diagrams for annual energy generation and the loss percentage of annual energy generation due to location restrictions in different locations have been generated in the end. Based on the findings of the GUI application, the PV panels in all locations in Malaysia tend to be placed in the position viii that faces West to achieve the highest annual energy output. Additionally, the comparisons among three cases have been performed, which are Case 1: optimum annual energy generation based on optimal tilt angles, Case 2: optimum annual energy generation based on optimal tilt angle and azimuth angle faces South, and Case 3: optimum annual energy generation based on tilt angle according to location’s latitude coordinate and azimuth angle faces South. At the end, it can be concluded that the top priority to obtain the optimum annual energy generation will be Case 1, by following with Case 3 and Case 2.